EDMH: Efficient discrete matrix factorization hashing for multi-modal similarity retrieval. Issue 3 (May 2023) - Yang, Fan; Ding, Xiaojian; Ma, Fumin; Tong, Deyu; Cao, Jie
Abstract: Hashing has been an emerging topic and has recently attracted widespread attention in multi-modal similarity search applications. However, most existing approaches rely on relaxation schemes to generate binary codes, leading to large quantization errors. In addition, amounts of existing approaches embed labels into the pairwise similarity matrix, leading to expensive time and space costs and losing category information. To address these issues, we propose an Efficient Discrete Matrix factorization Hashing (EDMH). Specifically, EDMH first learns the latent subspaces for individual modality through matrix factorization strategy, which preserves the semantic structure representation information of each modality. In particular, we develop a semantic label offset embedding learning strategy, improving the stability of label embedding regression. Furthermore, we design an efficient discrete optimization scheme to generate compact binary codes discretely. Eventually, we present two efficient learning strategies EDMH-L and EDMH-S to pursue high-quality hash functions. Extensive experiments on various widely-used databases verify that the proposed algorithms produce significant performance and outperform some state-of-the-art approaches, with an average improvement of 2.50% (for Wiki), 2.66% (for MIRFlickr) and 2.25% (for NUS-WIDE) over the best available results, respectively. Highlights: We develop an effective EDMH framework to achieve high-quality multi-modal hash codes. We conceive a semantic label offset embedded learning scheme. We design efficient optimization mechanism without any relaxation. We present two efficient learning strategies to pursue high-quality hash functions. Experimental results demonstrate the superiority of our method in accuracy and efficiency.